Chemical Properties Associated with Guts, Soil and Nest Materials of Odontotermes and Macrotermes Species from Kenya - Budambula, Nancy; Makonde, H. M.; Muwawa, E. M.; Osiemo, Z. L.; Boga, H. I. (Jomo Kenyatta University of Agriculture and Technology, 2010)
Changes in carbon and nitrogen cycles in tropical soils affect soil functioning and ecosystem activity. Termites play important roles in carbon and nitrogen cycles, thus determination of levels of such compounds is essential. This study was aimed at determining the levels of various forms of nitrogen, carbon and pH in the guts, soil and nest materials associated with Odontotermes and Macrotermes termite species. Macro- and micro-elements such as potassium, calcium, magnesium, phosphorus, zinc, manganese, iron and copper were also evaluated. The standard soil analyses and concentrations of various forms of nitrogen, carbon and pH in the samples were performed using calometric and Bremmer’s methods. Results showed the texture grade of the soils ranged between sandy clay loamy to loamy sand across the samples. The clay content for most mounds was comparably higher than in the surrounding soil. Most of the concentrations of ammonia, nitrate and total organic carbon between the termites and within the gut sections were significantly different (p < 0.05). This was observed between and within the termite mounds. Levels of ammonia (3.00 – 6.00 ppm) and nitrate (6.00 - 11.50 ppm) were highest in the hindguts of all termites analyzed than the respective foreguts and midguts sections. Notably, levels of ammonia (6.00 – 14.50 ppm), nitrate (16.00 – 83.00 ppm) and organic carbon (31.00 – 37.00 %) were highest in the fungus comb samples. Likewise, levels of all macro- and micro-elements investigated were highest in the fungus combs. anganese had the highest concentration (20.28 ppms) while copper had the least concentration (0.11ppms).
Keywords: Termites; mineralization; tropical soils; odontotermes; macrotermes